Corporate Governance in Accounting: A Bibliometric Analysis of Thematic Patterns and Citation Dynamics (2000–2026) - Loso Judijanto (West Science Accounting and Finance, 2026)
This study aims to map the intellectual structure, thematic evolution, and citation dynamics of corporate governance research within the accounting domain over the period 2000–2026. Using a bibliometric approach, data were collected from the Scopus database and analyzed using VOSviewer to examine publication trends, keyword co-occurrence, co-citation networks, and thematic developments. The results indicate that corporate governance functions as the central research theme, closely associated with key topics such as earnings management, audit quality, and financial reporting. Thematic clustering reveals a strong foundation in traditional governance mechanisms, including board structure, ownership concentration, and audit committees, which are primarily linked to firm performance and reporting quality. Furthermore, the findings highlight a significant shift toward emerging themes such as sustainability, corporate social responsibility (CSR), and environmental, social, and governance (ESG), reflecting a transition from shareholder-oriented to stakeholder-oriented perspectives. Citation analysis demonstrates the presence of influential authors and journals that shape the intellectual development of the field, while overlay visualization indicates that sustainability-related topics represent the most recent research frontier. This study contributes to the literature by providing a comprehensive mapping of corporate governance research in accounting and identifying key directions for future research, particularly in integrating sustainability and interdisciplinary perspectives into governance frameworks.